Upaya Kepala Sekolah dalam Mengatasi Dekadensi Moral Siswa Studi Kasus di SMK Harapan Bangsa Panti Kecamatan Panti, Kabupaten Pasaman - Efrita, Rika; Wiza, Rahmi (YASIN, 2024)
The rapid development of the times brings a negative side that is difficult to filter for the Indonesian nation, which affects the morals, attitudes and behavior of a person, especially for teenagers. Moral deviation or moral decadence is an erosion of identity related to the moral decline of religious values, nationalism, socio-cultural values and the development of individual morality. To minimize the phenomenon of student moral decadence that occurs, schools have a major role to suppress the growth of moral decadence turmoil among the increasingly uncontrollable progress of the times. One of the schools that has successfully overcome moral decadence and received an award for implementing pesantren-based character education from the education office is SMK Harapan Bangsa Panti, which is inseparable from the efforts of the school principal. Descriptive qualitative method with primary data in the form of interviews with principals and teachers and secondary data in the form of student agenda books, instruments used notebooks, voice recordings and researchers, data collection techniques interviews, observation and documentation and data analysis techniques are inductive with data reduction steps, data presentation and conclusion drawing. The results of this study show that the principal's efforts in overcoming moral decadence are prioritizing discipline, the school provides sanctions for those who violate the discipline, evaluates the school regulation program, runs a religious coaching program and the principal becomes a role model for all school members. The solution to the problems in overcoming moral decadence for adolescents is the principal's efforts in making various programs and running them in a structured and repetitive manner.